Examining the models of social entrepreneurs in Nam Noi community, Hat Yai district, Songkhla province - Parinyasutinun, Utai (Humanities, Arts and Social Sciences Studies, 2024)
This qualitative research aimed to exam the models of social entrepreneurs in the Nam Noi community, of Hat Yai district, Songkhla province. The qualitative methods of interview, focus group discussions, participant observation, and knowledge-sharing forums were used as field data collection tools. Informants for the research comprised 70 people, consisting of 3 social entrepreneurs, 25 villagers, 4 community leaders, 1 local administrative officer, 5 academics, 5 social movement activists, and 27 students. The data were also collected from related literature reviews and area studies. The data analysis was mainly based on the content analysis approach. The study found that social entrepreneurs in the Nam Noi community were entrepreneurs who operated businesses to respond to their own needs and to help solve community problems. Moreover, whether considering any of the models of social entrepreneurs, be it the pioneer, cooperator, social network creator, inspiration, or changemaker, all of them utilized social innovations such as social networks, computer programs, or online social media that impacted the community’s economic, social, and environmental aspects. They also corresponded with the sustainable development goals in the following aspects. First, people’s development resulted from academic cooperation through educational institutions. Second, the planet’s development resulted from the change in food containers. Third, prosperity and development resulted from the rotation of money, income distribution, and community economic stimulation. Fourth, peace development resulted from family strengthening, contributing to peace and happiness for people in the community. Fifth, partnership development resulted from the creation of social media networks for a better community. All of these innovations helped people in the community have a better quality of life.